Pengaruh Gaya Hidup, Label Halal dan Kesadaran Halal terhadap Keputusan Pembelian pada Coffee Shop - Nuha, Buja Lizammin; Anwar, Moch Khoirul (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the results of research on the influence of lifestyle, halal labels, and halal awareness on Coffee Shop purchasing decisions in Islamic Students of Surabaya State University. This study used descriptive quantitative methods through a sample of 80 students. The distribution of questionnaires was carried out by means of Likert scales on lifestyle, halal labels, and halal awareness. This study used multiple regression analysis using instrument data tests, classical assumption tests and hypothesis tests using t tests, f tests and coefficient of determination (r2) tests. The results of this study explain that partially the variables of lifestyle and halal awareness have a positive and significant influence on the variables tied to purchasing decisions, while the variables of halal labels do not have a positive and insignificant effect on variables bound to purchasing decisions. Then simultaneously lifestyle variables, halal labels, and halal awareness have a positive and significant influence on variables tied to purchasing decisions. The results of the coefficient of determination test (R Square) found that lifestyle, halal labels, and halal awareness had a simultaneous influence of 65.1% on Coffee Shop purchasing decisions in Islamic Students of Surabaya State University. Keywords: lifestyle; halal label; halal awareness; purchasing decision; coffee shop.